Acute hepatitis of unknown origin in children: A combination of factors - Gong, Kai; Xu, Xianbin; Yao, Junjie; Ye, Shaoheng; Yu, Xia; Tu, Huilan; Lan, Yan; Fan, Yu-chen; Shi, Yu (Frontiers in Pharmacology, 2022)
On April 5, 2022, the World Health Organization was notified of 10 cases of severe acute hepatitis of unknown etiology in children under 10 years of age in the United Kingdom. Although the exact cause of a proportion of pediatric acute hepatitis and acute liver failure cases was unclear, the above event has caused widespread concern worldwide. As of September 14, 2022, approximately 1296 probable cases of acute hepatitis of unknown etiology have been reported from 37 countries/regions, of which approximately 55 required or received liver transplantation and 29 died. Although the etiology of acute hepatitis of unknown origin in children remains unclear, many hypotheses have been proposed about the disease. Instead of individual factors such as "adenovirus infection", "SARS-CoV-2 related", and "Adeno-associated virus 2 with helper virus coinfection", it is more likely due to a combination of factors. Accordingly, there is an urgent need for more data and research to clarify the disease etiology. This review aims to provide a historical perspective of acute hepatitis of unknown etiology in children in the past decades and summarize the current hypothesis and evidence on this emerging disease.